Pengaruh DER, ITO, Dan Sales Growth Terhadap Financial Distress Perusahaan Sektor Healthcare - Elviendo Johanda Pratama; Trisnadi Wijaya (MDP Student Conference, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Inventory Turnover, and Sales Growth on Financial Distress in healthcare sector companies listed on the Indonesia Stock Exchange during 2020–2024. Financial Distress is measured using the modified Altman Z’’-Score model. This research employs a quantitative approach using secondary data obtained from annual financial statements. The sample is selected using a purposive sampling method. Data analysis is conducted using multiple linear regression with SPSS. The results indicate that Debt to Equity Ratio and Inventory Turnover have a negative and significant effect on Finansial Distress, while Sales Growth has a positive and significant effect. Simultaneously, all independent variables significantly affect Financial Distress. The findings are expected to provide useful insights for management and investors in assessing financial risk in the healthcare sector.